Changes in cerebral vascular reactivity and structure following prolonged exposure to high altitude in humans. Issue 12 (10th December 2015) - Foster, Glen E.; Davies‐Thompson, Jodie; Dominelli, Paolo B.; Heran, Manraj K. S.; Donnelly, Joseph; duManoir, Gregory R.; Ainslie, Philip N.; Rauscher, Alexander; Sheel, A. William
Abstract: Although high‐altitude exposure can lead to neurocognitive impairment, even upon return to sea level, it remains unclear the extent to which brain volume and regional cerebral vascular reactivity (CVR) are altered following high‐altitude exposure. The purpose of this study was to simultaneously determine the effect of 3 weeks at 5050 m on: (1) structural brain alterations; and (2) regional CVR after returning to sea level for 1 week. Healthy human volunteers ( n  = 6) underwent baseline and follow‐up structural and functional magnetic resonance imaging (MRI) at rest and during a CVR protocol (end‐tidal PCO2 reduced by −10, −5 and increased by +5, +10, and +15 mmHg from baseline). CVR maps (% mmHg −1 ) were generated using BOLD MRI and brain volumes were estimated. Following return to sea level, whole‐brain volume and gray matter volume was reduced by 0.4 ± 0.3% ( P  < 0.01) and 2.6 ± 1.0% ( P  < 0.001), respectively; white matter was unchanged. Global gray matter CVR and white matter CVR were unchanged following return to sea level, but CVR was selectively increased ( P  < 0.05) in the brainstem (+30 ± 12%), hippocampus (+12 ± 3%), and thalamus (+10 ± 3%). These changes were the result of improvement and/or reversal of negative CVR to positive CVR in these regions. Three weeks of high‐altitude exposure is reflected in loss of gray matter volume and improvements in negative CVR. Abstract : We investigated the impact of high altitude exposure on regional cerebral vascular function and cerebral tissue volumes following return to the normoxic environment. High altitude exposure led to improvements in regional cerebral reactivity depending upon the regional reactivity at baseline. In addition, grey matter volume was selectively reduced in otherwise healthy individuals.